Terapia comunitária integrativa : cuidado a pessoas que vivenciam a doença falciforme - Figueiró, Alessandra Varinia Matte (2016)
The Integrative Community Therapy (ICT) works as a community space for sharing life experiences performed in a horizontal and circular way. For people who experience sickle-cell disease, the use of ICT shows relevant to excite the problematization of this sickening situation, allowing reflecting about the reality and its contradictions. Therefore, this study aims to understand how care effective is the ICT, to people who experience sickle-cell disease. This is a qualitative research, guiding by the interface search with the intervention. The location of the study was a public blood center in the city of Cuiabá-MT. Participants were people who experience sickle-cell disease, attended in the public blood center, and participated in at least one ICT meeting, totalizing 33 participants. The empirical material was composed of the transcript of the meetings, which were recorded on audio and video, and field observation records. The study meets the ethical principles and the project is approved by the Research Ethics Committee under protocol number 921,261/CEP-HUJM/2014. The results showed that the ICT, as a space for exchanging experiences, helps sick people to acquire more knowledge about the disease, help in illness acceptance process, and also ICT has the potential for the formation of support networks. It was possible to evidence also, the experiences of people living with this illness process, their sufferings, difficulties and demands, the violation of rights that they faced, such as the health professional negligence before the user's pain, and also factors which difficult care, such as the lack of these professionals about the disease, and the prejudice they face, since sickle-cell disease has a higher incidence in black people. Through ICT we also evidenced the people coping ways before problems living with the illness and we realize the importance that the participants assigned to the meetings. Through the information obtained in these moments, several interventions in the studied reality were also performed. We conclude that this study contributed greatly to nursing, since it shows the hard struggle of people who experience sickle-cell disease in the quest for health care, as well as to expand the knowledge of professionals who provide health services, as this was one of the main demands of people with sickle-cell disease reported in ICT meetings.